HUBUNGAN ANTARA METODE ONLINE LEARNING (E-LEARNING) DENGAN MOTIVASI BERPRESTASI MAHASISWA UNIVERSITAS “XX” - Idah Niswati; A.K. Donna; Putri Lestari; Gustyani Gustyani (Universitas Bunda Mulia, 2012)
The concept underlying this study is a phenomenon that occurs in education today and in the future that can not be separated from the advances in communications technology and informatics.Traditional learning methods (non e-learning) is now insufficient to meet the needs and improve the student’s achievement motivation to be ready to compete in the corporate world. Therefore, several universities have started to apply the methods of online learning (e-learning). This study aims to determine the relationship of online learning methods (e-learning) and traditional (non e-learning) with students’ achievement motivation at Bunda Mulia University. The data is collected using a questionnaire with Likert scale that is closed and 2 open-ended items. The validity and reliability of the items are tested using Cronbach Alpha. The population in this study is made up of all the students of the Bunda Mulia University from the year 2008-2011 from eleven Study Programs, while the sample is five active students from each year, i.e. 2008, 2009, 2010, and 2011 in eleven Programs. The total number of samples is 220 students. The data is analyzed using Pearson Correlation and then further analyzed using t-test with the aid of SPSS version 17.0. The results showed a significant correlation between the variables (X1), and (X2) and Y, F = 60.595, R = 0.359, p = 0.000. The hypothesis that there is a relationship between the methods of online learning (e-learning) and traditional learning methods (non e-learning) is correlated positively with the achievement motivation is received. Keywords : methods of online learning (e-learning), traditional (non e-learning), achievement motivation, student